1985
DOI: 10.1016/0167-2584(85)90844-8
|View full text |Cite
|
Sign up to set email alerts
|

Multilayer distortion in the reconstructed (110) surface of Au

Abstract: A new LEED intensity analysis of the reconstructed Au(110)-(1×2) surface results in a modification of the missing row model with considerable distortions which are at least three layers deep. The top layer spacing is contracted by about 20%, the second layer exhibits a lateral pairing displacement of 0.07 .~ and the third layer is buckled by 0.24 ,~. Distortions in deeper layers seem to be probable but have not been considered in this analysis. The inter-atomic distances in the distorted surface region show bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Moreover, in the missing-row reconstruction, the contraction of the topmost layer is usually accompanied by a lateral pairing of the atomic position in the plane below. 39 The shift of two rows under the missing row was found to be closer from 3 ± 1% and those under the filled one was farther so that the average distance remains the same as that in the alloy (3.94 Å). The interplanar dilatations induced by gold enrichment of planes −1 and −2 are negligible in the frame of the accuracy of these fits.…”
Section: ■ Resultsmentioning
confidence: 81%
“…Moreover, in the missing-row reconstruction, the contraction of the topmost layer is usually accompanied by a lateral pairing of the atomic position in the plane below. 39 The shift of two rows under the missing row was found to be closer from 3 ± 1% and those under the filled one was farther so that the average distance remains the same as that in the alloy (3.94 Å). The interplanar dilatations induced by gold enrichment of planes −1 and −2 are negligible in the frame of the accuracy of these fits.…”
Section: ■ Resultsmentioning
confidence: 81%
“…2a–c ). Clean Au(110) exhibits a (1 × 2) surface reconstruction (Au-(1 × 2)), also called ‘missing-row' 20 21 , which is unaffected by O adsorption at coverages considered here 22 . It consists of alternate troughs and ridges in the [1–10] direction, which appear as bright lines in STM.…”
Section: Resultsmentioning
confidence: 99%
“…The origin of the reconstruction of (110) surfaces of transition metals like Ir, Pt, and Au has been of great interest to surface science since its first observation 50 years ago. Such reconstructions may occur for the clean surface. Of particular importance to catalysis are surface reconstructions induced by adsorbates. For instance, it has been shown that for Au and Pt a (1 × 2)-missing-row structure has a lower surface energy than the corresponding (110) surfaces .…”
Section: Introductionmentioning
confidence: 99%